2020
DOI: 10.1128/mra.00641-20
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequence of Bacillus subtilis WS1A, a Promising Fish Probiotic Strain Isolated from Marine Sponge of the Bay of Bengal

Abstract: This study reports the draft genome sequence of a promising fish probiotic, Bacillus subtilis strain WS1A, that possesses antimicrobial activity against Aeromonas veronii and suppressed motile Aeromonas septicemia in Labeo rohita. The de novo assembly resulted in an estimated chromosome size of 4,148,460 bp, with 4,288 open reading frames.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Application of both consortium and individual bacteria with formulated fish feed significantly improved growth, hematological, and reproductive performances of the host fishes compared to the untreated control. Although enhancement of growth and disease resistance in fish treated with probiotic bacteria have been reported by several researchers 12 , 14 17 , this study for the first time demonstrated that gut probiotic bacteria such as GFB-1 , GFB-2, GFB-3, GFB-4, and GFB-5 belonging to the genera of Enterococcus, Pseudomonas, Bacillus , and Citrobacter isolated from B. gonionotus significantly improved the growth, hematological and reproductive performances of the host fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of both consortium and individual bacteria with formulated fish feed significantly improved growth, hematological, and reproductive performances of the host fishes compared to the untreated control. Although enhancement of growth and disease resistance in fish treated with probiotic bacteria have been reported by several researchers 12 , 14 17 , this study for the first time demonstrated that gut probiotic bacteria such as GFB-1 , GFB-2, GFB-3, GFB-4, and GFB-5 belonging to the genera of Enterococcus, Pseudomonas, Bacillus , and Citrobacter isolated from B. gonionotus significantly improved the growth, hematological and reproductive performances of the host fish.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial diseases hamper the colossal amount of fish production in aquaculture, and application of the chemicals such as antibiotics in health management is commonly practiced 11 . Antibiotics are applied as a traditional strategy to control bacterial fish diseases such as motile Aeromonas septicemia in freshwater and also for improving growth performances 12 , 13 . More than 70% of antibiotics are used in aquaculture operations wind up in the environment and plasmid carrying resistance genes can be transferred from fish pathogen to humane pathogens 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Probiotic bacilli have been reported to greatly improve the quality of water by preserving the equilibrium of several physicochemical parameters, regulating of the composition and abundance of microbial species by antagonism, decomposing various organic waste, and keeping the ecosystem safe for aquaculture [ 139 ]. It is evident that Bacillus has a huge potential to contribute to the sustainability of fish farming by improving water quality and preserving the total welding of cultivated fish such as growth improvement, feed usage, immune system responses, and defense against infectious diseases, especially infection by pathogenic bacteria [ 8 ].…”
Section: Application Of Probiotics In Livestockmentioning
confidence: 99%
“…Spore-forming probiotics that are beneficial for animals have been reported as being isolated from soil ( 1 ), aquatic systems ( 2 ), and other sources, such as fermented dairy products ( 3 ). It has been reported that the spores of many Bacillus strains germinate and proliferate in the intestine of animals ( 4 8 ) and can sporulate in the lower intestine ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%